Art education needs a curriculum paradigm shift. Issue 2 (1st August 2021) - Lawton, Pamela Harris
From your perspective, what is the place of social justice education (and politics) in the art classroom? Are these topics a distraction from the disciplinary content of visual arts education, as you understand it? From your perspective, what is the disciplinary content of art education?